Ženski pari moških poimenovanj v slovenskem knjižnem jeziku 16. stoletja - Merše, Majda (Slavia Centralis, 2020)
Feminine pairs of masculine designations in the Slovenian literary language of the 16th century The paper discusses the usage of feminine designations in 16th century standard Slovenian by presenting their basic semantic groups and formational patterns. Feminine pairs of masculine designations, in comparison with masculine pairs, are examined based on semantic symmetry and the frequency of use. The paper presents and causally explains groups of just masculine and just feminine designations while discussing the manner in which representatives of groups composed of masculine and feminine elements were selected.